An Analysis Of Public Service Delivery At Perumda Tirta Hidayah Bengkulu City - Saputra, Harius Eko; Lorita, Evi; Aprianti, Resi Dwi (Journal of Research in Social Science and Humanities, 2022)
This study aims to analyze the level of public service responsiveness at Perusahaan Umum Daerah (Perumda) Tirta Hidayah in Bengkulu City, with a focus on new water connection services. A descriptive qualitative method was employed, using in-depth interviews, direct observation, and document analysis as data collection techniques. The findings indicate that the current level of service responsiveness is suboptimal. Customers reported delays in connection installation, inconsistent information, and slow responses to complaints. The main contributing factors include limited human resources and the absence of an integrated service system based on information technology. The analysis draws on Dwiyanto’s theory of public service responsiveness, which highlights five key indicators: customer complaints, bureaucratic attitudes, feedback utilization, corrective action, and the role of citizens in the service system. The study recommends a comprehensive reform of the service system, enhancement of human resource capacity, and increased community involvement to achieve responsive, transparent, and citizen-oriented public services.